Designer Nonplanar Porphyrins with Tuned Properties for Application as Bifunctional Organocatalyst - Roucan, Marie (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
The aim of this research was to investigate the use of different free base nonplanar porphyrins as bifunctional catalysts. This involved the tailored design of various porphyrin catalysts and the subsequent testing of said systems in catalytic screening reactions with small organic molecules. Porphyrins are a unique class of natural compounds that are omnipresent in nature. This results in them being involved in many important biological processes for example oxygen transport, electron transfer and oxidation reactions as well as photosynthesis. These versatile molecules can also be found in cofactors in nature and are crucial regulatory effectors in many biochemical processes. Nowadays the chemistry of porphyrins is well established and they can be found in a wide area of applications. However, porphyrins usually act as a simple ligands where the actual desired effect is subsequent to the formation of a tetrapyrrole metal complex. Most of the time the very interesting inner core N and NH units are deemed inaccessible, albeit they could offer an interesting entry point to a plethora of new applications and reactions. This work focuses on taking advantage of these active inner units of the porphyrin by purposely fine-tuning and modulating the porphyrin periphery and hence making these formerly esoteric units available through the introduction of precise distortion to the porphyrin macrocycle. This is envisioned to lead to distorted free base tetrapyrroles that have tuneable properties and form complexes through weak interactions of the core with other molecules and therefore represent interesting candidates for organocatalysts. In order to achieve this goal the project was divided into two main parts: a) The synthesis of a library of nonplanar porphyrins with various degrees of distortion. b) The investigation into the activity of these molecules as effective catalysts in 1,4-addition reactions. The first method employed to obtain the essential distortion of the porphyrin macrocycle and thus make the N and NH units of the porphyrin macrocycle available for catalytic activity was through crowding of the periphery of the porphyrin core. The synthesis of a large library of nonplanar highly substituted porphyrins was then achieved through condensation reactions. Therefore, a series of aldehydes with different electron donating substituents were chosen together with two types of substituted pyrrole units resulting in two families of highly substituted porphyrins. The electron donating effects of the respective aldehydes were quantified using Hammett?s values to strategically design and fine-tune the electronic properties of the porphyrin macrocycles. The strong electron donating effects of the substituents on the aryl units decreases the electrophilicity of the aldehyde group and thus its reactivity towards pyrrole molecules. More importantly the presence of strong electron donating groups induces a very high basicity to the inner core functional groups of the porphyrin, which could result in an enhanced reactivity toward binding of small molecules. Five new products were obtained which are promising candidates for the application as organocatalysts as they all possess the necessary requirements, namely a high degree of distortion and enhanced electron density of their macrocycle. Depending on the aldehyde used and the position of the substituents on the aldehyde (para, meta, ortho) yields of the porphyrin ranged from moderate to high. In some cases, no product formation was observed. One of these compounds was the p-dimethylamino-OETArX-porphyrin, which would be due to its electronic nature. As condensation reactions proved unsuccessful, other functionalization reactions, such as Buchwald-Hartwig reactions or reductions, were investigated. The spectral properties of the porphyrins were investigated by UV-vis and NMR spectroscopy. Furthermore, X-ray analysis showed some interesting results such as a cage formed by a dicationic porphyrin and acetic acid molecules, revealing possible binding abilities for various anions. Another way of introducing distortion to a porphyrin macrocycle is via methylation of the inner nitrogen atoms of planar free base porphyrins. This results in a considerable distortion of the macrocycle. A library of N-methylated porphyrins with various aryl substituents was successfully synthesized. Optimizations of the methylation reaction were undertaken resulting in not only increased yields but also in the introduction of a precise and defined number of methyl groups to the porphyrin core. This allows for the tailored synthesis of N-methylated porphyrins bearing one to three methyl units in the porphyrin macrocycle. The efficiency and regioselectivity of the methylation are correlated to the peripheral substitution pattern. Additionally, the electron donating properties of the substituents tend to enhance the reactivity, while electron withdrawing groups lower the efficiency of the methylation reaction. Even so, yields of up to 95% were obtained. Furthermore, the very characteristic spectroscopic profiles of N-methylated porphyrins in both NMR and UV-vis spectroscopy were investigated, showcasing the correlation between the chemical and bathochromic shifts and the structural conformation of the porphyrins synthesized. Comparison of X-ray structures of porphyrins synthesized and literature known structures of the planar free base and nonplanar N-substituted porphyrins revealed that, from a structural point of view, N-methylation of planar porphyrins results in significant structural changes and a notable macrocycle distortion resulting in a similar distortion to that of a highly substituted porphyrin. NSD was successfully applied to all structures and used to determine the distortion modes in porphyrin structures with an increasing number of N-substitutents. Finally, the porphyrins synthesized in the previous chapters were tested for their catalytic activity. A sulfa-Michael addition reaction was selected as the catalytic test reaction of choice. Initial screening reactions were undertaken using the N21-monomethylated tetraphenylporphyrin. As some conversion to desired target compound was observed during the initial reaction conditions (9%), optimizations of parameters such as; solvent, catalyst loading, concentration of the reaction, etc. were explored in order to achieve better yields and to establish standard reaction conditions to then reliably screen a panel of porphyrins. Screening of the porphyrin libraries revealed that in order for free base porphyrins to be catalytically active they require a) a high distortion of the macrocycle, b) an electron rich density of the porphyrin core and c) the availability of the amine and imine moieties. Considering these requirements, up to quantitative yields were achieved with some candidates of the prepared porphyrin library. Furthermore the mechanism of the porphyrin catalyst was explored. The initial results suggested a bifunctional catalytic activation of both the Michael acceptor and the nucleophile, with the monoprotonated porphyrin being the catalytically active species during the process. In order to confirm this mode of action, different spectroscopic studies were undertaken such as protonation studies of the porphyrin catalysts and activation studies of the electrophile. Further investigation of a range of different electrophiles were carried out in order to test the sensitivity of the catalysts. All electrophiles tested gave positive results with very high conversion up to quantitative yields. The most active catalyst in the Michael addition reactions was then trialled as a possible catalyst in Aldol and Diels-Alder reaction. Unfortunately, no activity was observed. In order to explore the role of basicity of the macrocycle further two families of catalysts with very high distortion and very strong electron donating groups were screened for their catalytic activity. It was revealed that these so-called ?super bases? were not catalytically active anymore. At a certain point, the increased basicity of the porphyrin macrocycle resulted in inactivation of the porphyrin in the present conditions established, due to the instant protonation of the porphyrin by the acidity of the solvent. Thus, careful considerations and design of the porphyrin macrocycle are quintessential when using free base porphyrins as catalysts.
APPROVED
Keywords: porphyrins; nonplanar porphyrins; spectroscopic analysis; conformation analysis; organocatalysis; michael additions; hydrogen bond; basicity